Restoring species diversity: assessing capacity in the U.S. native plant industry. Issue 4 (16th April 2018) - White, Abigail; Fant, Jeremie B.; Havens, Kayri; Skinner, Mark; Kramer, Andrea T.
Abstract : Large quantities of diverse and appropriately adapted native plant germplasm are required to facilitate restoration globally, yet shortages can prevent restorations from attaining desired species diversity and structure. An extensive native plant industry has developed in the United States to help meet these demands, yet very little is known about its capacity to support germplasm needs. To better understand current capacity and germplasm availability, we report results of the first comprehensive and quantitative assessment of the native plant industry in the United States, which includes at least 841 vendors nationwide and the species they make available for restoration. We synthesized lists of commercially available species from native plant vendors across the United States and identified gaps in species availability to inform germplasm research, development, and production. Of the approximately 25, 000 vascular plant taxa native to the United States, 26% are sold commercially, with growth form, conservation status, distribution, and taxonomy significantly predicting availability. In contrast, only 0.07% of approximately 3, 000 native nonvascular taxa are sold commercially. We also investigated how demand for germplasm to support high‐quality restoration efforts is met by vendors in the Midwestern tallgrass prairie region, which has been targeted extensively by restoration efforts for decades. In this well‐developed native plant market, 74% of more than 1, 000 target species are commercially available, often from vendors that advertise genetically diverse, locally sourced germplasm. We make recommendations to build on the successes of regional markets like the tallgrass prairie region, and to fill identified gaps, including investing in research to support production, ensuring more consistent and clear demand, and fostering regional collaboration.